Developing an Explicit Instruction Special Education Teacher Observation Rubric. (May 2019) - Johnson, Evelyn S.; Zheng, Yuzhu; Crawford, Angela R.; Moylan, Laura A.
In this study, we developed an Explicit Instruction special education teacher observation rubric that details the elements of explicit instruction and tested its psychometric properties using many-facet Rasch measurement (MFRM). Video observations of classroom instruction from 30 special education teachers across three states were collected. External raters ( n = 15) were trained to observe and evaluate instruction using the rubric and assigned scores of "implemented, " "partially implemented, " or "not implemented" for each of the items. Analyses showed that the item, teacher, lesson, and rater facets achieved high psychometric quality for the instrument. Implications for research and practice are discussed.